2008
DOI: 10.1002/ajhb.20744
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms in the cadherin 23 (CDH23) gene in Polish workers exposed to industrial noise

Abstract: Single nucleotide polymorphisms (SNPs) are the most frequent type of variation in the human genome and may underlie differential susceptibility to common genetic diseases. A candidate gene for susceptibility to noise-induced hearing loss (NIHL) is Cadherin 23 (CDH23). This study aimed to analyze genetic variation in the CDH23 gene in a group of 10 individuals derived from a cohort of 949 workers exposed to noise, and consisted of five persons from each of the resistant and susceptible extremes. DNA samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
3
15
0
1
Order By: Relevance
“…An interesting implication of our findings is that some CDH23 mutations may predispose individuals to hearing loss caused by mechanical insults. In fact, polymorphisms in CDH23 are associated with noise-induced hearing loss (43), and mice heterozygous for the Cdh23 waltzer allele show increased noise susceptibility (44). Finally, a polymorphism in Cdh23 is associated with age-related hearing loss (14), which may be related to instability of tip links.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting implication of our findings is that some CDH23 mutations may predispose individuals to hearing loss caused by mechanical insults. In fact, polymorphisms in CDH23 are associated with noise-induced hearing loss (43), and mice heterozygous for the Cdh23 waltzer allele show increased noise susceptibility (44). Finally, a polymorphism in Cdh23 is associated with age-related hearing loss (14), which may be related to instability of tip links.…”
Section: Discussionmentioning
confidence: 99%
“…These include a variety of metabolic enzymes and heat shock proteins tied to redox regulation (Yang, et al, 2006; Konings, et al 2007; Lin, et al, 2010; Liu, et al, 2010a, b; Abreu-Silva, et al, 2011), ion channels and ion transport proteins, and structural and gap junction proteins (Van Laer, et al, 2006; Konings, et al, 2007; Slwinska-Kowalska, et al, 2008; Pawelczyk, et al, 2009). , These findings have been replicated for catalase (CAT) the heat shock protein HSP70, potassium ion channels (KCNQ4, KCNE1), myosin 14 (MYO14) and protocadherin 15 (PCDH15).…”
Section: Introductionmentioning
confidence: 99%
“…[65][66][67][68] For example, Pawełczyk et al, [66] suggested a possible role of potassium-recycling pathway genes in determining the individual susceptibility to NIHL. Another candidate gene for NIHL susceptibility is cadherin 23 (CDH23), which is a component of the inter-stereocilia links on the cochlear hair cells.…”
Section: Polandmentioning
confidence: 97%
“…Another candidate gene for NIHL susceptibility is cadherin 23 (CDH23), which is a component of the inter-stereocilia links on the cochlear hair cells. [65] In the Nofer Institute of Occupational Medicine, Lodz, Poland, apart of human studies, animal research had been performed in the past on guinea pig, chick, and mouse models under the leadership of Mariola Śliwińska-Kowalska. The morphological changes in the guinea pig's cochlea examined after exposures to noise using the light and electron microscopy were described.…”
Section: Polandmentioning
confidence: 99%